The many facets of information systems (+projects) success - Varajão, João (2018)
It is well accepted that Information Systems (IS) are critical for the competitiveness of virtually any human organization. However, IS need constant attention to fulfill their role and to keep pace with the changes of organizations. Therefore, the success of IS projects is crucial for the success of IS and, consequently, for the success of the organizations themselves since they are closely related. Given the complex nature of the participating objects and related concepts (e.g., people, information, processes, and technology), the perspectives of success and its influencing factors can be of high complexity. This complexity comes from various aspects that need to be recognized, considered and evaluated, as well as from the multiple interactions that occur between them. This article aims to contribute with new insights and a new way of addressing the success of projects and IS, by identifying and describing various important facets of success.